Visceral Adipose Tissue was Associated with Increased Risk of Insulin Resistance in Lean Polycystic Ovarian Syndrome, Independent with Retinol Binding Protein-4: Jaringan Adiposa Viseral berkaitan dengan Peningkatan Risiko Resistensi Insulin pada Sindrom Ovarium Polikistik dengan Indeks Masa Tubuh Normal, Independen terhadap Retinol Binding Protein-4 - Vita Silvana; Andon Hestiantoro; Muharam Natadisastra; Kanadi Sumapraja; Budi Wiweko (Indonesian Socety of Obstetrics and Gynecology, 2020)
Objective: To determine whether visceral adipose tissue or serum RBP-4 were related with the risk increment of insulin resistance in normal BMI PCOS patients. Methods: This was a cross-sectional study conducted in normal body mass index PCOS patients at Yasmin Clinic, RSCM, Jakarta from July 2014 until March 2015. Diagnosis of PCOS was established using Rotterrdam (2003) criteria. Insulin resistance was confirmed by using ratio of HOMA-IR >1.4. Results: Among 40 subjects, 20 subjects (50%) belong insulin resistance group. Serum RBP-4 level was higher in insulin resistance group (p=0.06). After ROC analysis was conducted, area under curve for of serum RBP-4 was 69.9% (CI 95% -3754.77 - (186.60-7696.14, p=0.061)). Cut-off level of serum RBP-4 was 23814.5 ng/mL yielded sensitivity and specificity to a level of 60% and 60%, respectively. After logistic regression were analyzed, visceral adipose tissue demonstrated substantial association with the risk increment of insulin resistance in normal BMI PCOS patients. Conclusions: Visceral adipose tissue demonstrated substantial association with the risk increment of insulin resistance in normal BMI PCOS patients, independent with serum RBP-4 levels. Key words: body mass index, diagnosis, insulin resistance, PCOS, retinol binding protein-4 Abstrak Tujuan: Untuk menentukan apakah jaringan adiposa viseral atau serum RBP-4 berhubungan dengan peningkatan risiko resistensi insulin pada Sindrom Ovarium Polikistik dengan indeks masa tubuh normal. Metode: Studi potong lintang dilakukan pada subjek SOPK dengan IMT normal di Klinik Yasmin, RSCM, Jakarta sejak Juli 2014 sampai dengan Maret 2015. Penegakan diagnosis SOPK dilakukan dengan kriteria Rotterdam (2003). Resistensi insulin dikonfirmasi dengan pemeriksaan rasio HOMA-IR > 1.4 Hasil: Diantara 40 subjek, sebanyak 20 subjek (50%) mengalami resistensi insulin. Kadar serum RBP-4 lebih tinggi pada kelompok resistensi insulin (p=0.06). Setelah dilakukan analisis Receiver Operating Curve (ROC), serum RBP-4 memiliki Area Under the Curve (AUC) sebesar 69.9% (IK 95% -3754.77 - (186.60-7696.14, p=0,061)). Titik potong kadar serum RBP-4 adalah 23814.5 ng/mL dengan sensitivitas dan spesifisitas masing-masing 60% dan 60%. Setelah dilakukan analisis regresi logistik, jaringan adiposa viseral menunjukan asosiasi yang kuat dengan terjadinya resistensi insulin pada pasien SOPK dengan IMT normal. Kesimpulan: Jaringan adiposa viseral menunjukan asosiasi yang kuat dengan terjadinya resistensi insulin pada SOPK dengan IMT normal, independen terhadap kadar serum RBP-4. Kata kunci: diagnosis, indeks masa tubuh, resistensi insulin, retinol binding protein-4, SOPK